DEVELOPMENT OF AN IoT-BASED KNEE EXOSKELETON DEVICE FOR REHABILITATION THERAPY MONITORING - Mohd Razali Sapiee; Theo Tiphshan Raj Thomas; Mohammad Hamiruce Marhaban; Asnor Juraiza Ishak; Miskon, Muhammad Fahmi Miskon (Asian Journal Of Medical Technology, 2023)
The COVID-19 pandemic has presented a multitude of challenges pertaining to medical treatments and patient care, creating a pressing need for innovative solutions. Constrained outdoor activities have hindered patients’ ability to access essential healthcare, while healthcare professionals encounter difficulties in remotely monitoring and administering treatments. This study aims to address these pressing issues by proposing an Internet of Things (IoT)-based exoskeleton system designed for the monitoring of knee rehabilitation therapy. Through the utilization of the IoT platform ThingSpeak, this developed system enables patients to remotely monitor the status of their knee recovery from the comfort of their homes. The collected data is securely stored and made accessible to healthcare professionals, facilitating remote analysis and the formulation of treatment recommendations. This pioneering solution amalgamates advancements in exoskeleton technology with seamless IoT integration, establishing a dependable and easily accessible framework for the monitoring of knee rehabilitation. By empowering patients to actively participate in their own recovery process and enabling remote monitoring by healthcare providers, this system effectively surmounts the limitations imposed by the pandemic and financial constraints. The proposed IoT-based exoskeleton system possesses the potential to revolutionize knee rehabilitation therapy, thereby enhancing patient engagement, optimizing treatment outcomes, and circumventing traditional healthcare barriers.